Synthesis and antiradical activity of alkyl derivatives of 5-(5-methyl-1h-pyrazol-3-yl)-4-phenyl-4h1,2,4-triazole-3-thiol - Gotsulya, A.; Гоцуля, Андрій Сергійович (My University, 2020)
Objective: The aim of the work was to develop effective methods for the synthesis of biologically active heterocyclic systems containing 1,2,4-triazole and pyrazole. Material and Method: Chemical structures of synthesized compounds were characterized with elemental analysis, IR, 1H-NMR, LC-MS techniques. The antiradical activity was evaluated using the 2,2-diphenyl-1- picrylhydrazyl (DPPH) radical scavenging activity assay. Result and Discussion: Developed optimal methods of obtaining of alkylderivatives of 5-(5-methyl-1Hpyrazol-3-yl)-4-phenyl-4H-1,2,4-triazole-3-thiol. A number of synthesized compounds showed moderate antiradical activity.
Keywords: antiradical activity; pyrazole; synthesis; 1,2,4-triazoles